2,5-Dihydroxyacetophenone Induces Apoptosis of Multiple Myeloma Cells by Regulating the MAPK Activation Pathway - Ko, Jeong-Hyeon; Lee, Jae Hwi; Jung, Sang Hoon; Lee, Seok-Geun; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Yang, Woong Mo; Um, Jae-Young; Sethi, Gautam; Ahn, Kwang Seok (MDPI, 2017)
2,5-Dihydroxyacetophenone (DHAP) is an active compound obtained from Radix rehmanniae preparata, which is widely used as a herbal medicine in many Asian countries. DHAP has been found to possess anti-inflammatory, anti-anxiety, and neuroprotective qualities. For the present study, we evaluated the anti-cancer effects of DHAP on multiple myeloma cells. It was discovered that DHAP downregulated the expression of oncogenic gene products like Bcl-xl, Bcl-2, Mcl-1, Survivin, Cyclin D1, IAP-1, Cyclin E, COX-2, and MMP-9, and upregulated the expression of Bax and p21 proteins, consistent with the induction of G2/ M phase cell cycle arrest and apoptosis in U266 cells. DHAP inhibited cell proliferation and induced apoptosis, as characterized by the cleavage of PARP and the activation of caspase-3, caspase-8, and caspase-9. Mitogen-activated protein kinase (MAPK) pathways have been linked to the modulation of the angiogenesis, proliferation, metastasis, and invasion of tumors. We therefore attempted to determine the effect of DHAP on MAPK signaling pathways, and discovered that DHAP treatment induced a sustained activation of JNK, ERK1/2, and p38 MAPKs. DHAP also potentiated the pro-apoptotic and anti-proliferative effects of bortezomib in U266 cells. Our results suggest that DHAP can be an effective therapeutic agent to target multiple myeloma.
Keywords: NF-KAPPA-B; INHIBITS PROLIFERATION; SIGNALING PATHWAYS; TERMINAL KINASE; GENE-PRODUCTS; CANCER; P38; GROWTH; CYCLE; ERK